C302: a multiscale framework for modelling the nervous system of Caenorhabditis elegans. (10th September 2018) - Gleeson, Padraig; Lung, David; Grosu, Radu; Hasani, Ramin; Larson, Stephen D.
Abstract : The OpenWorm project has the ambitious goal of producing a highly detailed in silico model of the nematode Caenorhabditis elegans . A crucial part of this work will be a model of the nervous system encompassing all known cell types and connections. The appropriate level of biophysical detail required in the neuronal model to reproduce observed high-level behaviours in the worm has yet to be determined. For this reason, we have developed a framework, c302, that allows different instances of neuronal networks to be generated incorporating varying levels of anatomical and physiological detail, which can be investigated and refined independently or linked to other tools developed in the OpenWorm modelling toolchain. This article is part of a discussion meeting issue 'Connectome to behaviour: modelling C. elegans at cellular resolution'.